Analisis Dampak Relokasi Pasar Tradisional Terhadap Pendapatan Pedagang Pasar Mejayan Baru Kabupaten Madiun - Yeny Susanty; Muchtar; Junaedi (Journal of Public Power, 2021)
The traditional market is an ancestral heritage market and has existed from time to time. Traditional market conditions are required to be equated with various policies, especially regarding cleanliness, tidiness, security, and comfort for buyers. The purpose of this study was to analyze the impact of traditional market relocation for buyers and on the income of traders in the Mejayan Baru market, Madiun Regency. This research uses a qualitative descriptive approach and is a field research. With the research location in the Caruban Regional Market, the address is JL Letjen Sutoyo, No. 1, Bangunsari, Mejayan, Caruban, Karanglo, Buduran, Madiun Regency. The specified informants were selected randomly. Data were collected by means of documentation, observation and interviews. Meanwhile, data processing and analysis techniques use data reduction, data display, and conclusion drawing and verification. The results of the research are as follows: After a market relocation, buyers in the Mejayan Baru market are reduced. because of the difficulty of transportation access to traditional markets, the quiet environment to the market which makes it prone to crime. The purchase price is slightly different from before the relocation, the positive impact felt by the community is the opening of job opportunities and a change in the status of illegal traders to legal and the negative impacts that arise are the decrease in the income of traders to half of the income before the relocation, the decrease in the feasibility and convenience of the business, increasing costs operational.